2000
DOI: 10.1046/j.1523-1739.2000.98585.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass Differences among Male Mangabey Monkeys Inhabiting Logged and Unlogged Forest Compartments

Abstract: Remedies for reduction in primate numbers following rainforest habitat disturbance must incorporate understanding of how disturbance affects population biology. Between July 1996 and July 1998, I captured 31 adult male grey cheeked mangabeys (  Lophocebus albigena) from groups occupying logged and unlogged forest in Kibale National Park, Uganda. Captured males were weighed, measured, fitted with radiocollars, and radiotracked three to five times a week. Males from groups in the unlogged forest were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…For example, the prevalence and richness of gastrointestinal helminth infections and the magnitude of multiple infections were greater for redtail monkeys in logged areas than undisturbed forest (Gillespie et al 2005), and such infections have been linked to increased stress levels and declines in primate populations in forest fragments (Chapman et al 2006b). Male mangabeys in logged forests had lower body mass than males in unlogged forests (Olupot 2000), which may influence survivorship. A study of locomotion of red colobus in logged and unlogged habitats demonstrated that removing trees reduced canopy pathways and increased energetic demands, risks of falling, and perhaps predation risk (Gebo and Chapman 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence and richness of gastrointestinal helminth infections and the magnitude of multiple infections were greater for redtail monkeys in logged areas than undisturbed forest (Gillespie et al 2005), and such infections have been linked to increased stress levels and declines in primate populations in forest fragments (Chapman et al 2006b). Male mangabeys in logged forests had lower body mass than males in unlogged forests (Olupot 2000), which may influence survivorship. A study of locomotion of red colobus in logged and unlogged habitats demonstrated that removing trees reduced canopy pathways and increased energetic demands, risks of falling, and perhaps predation risk (Gebo and Chapman 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of food resources directly impacts health and body condition, which can affect birth and mortality rates, as well as susceptibility to predation and disease (Chapman et al 2005;Milton 1996;Olupot 2000). Resource distributions can affect ranging, e.g., groups may range farther when food density is lower, intragroup spacing, and behavioral patterns, including optimum group size, time budgets, dominance relationships, and rates of social behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Some have conducted studies from this perspective in reference to the changes initiated by logging Fairgrieve and Muhumuza, 2003;Olupot, 2000;Plumptre and Reynolds, 1994;Rao and van Schaik, 1997;Skorupa, 1988;Wilson and Wilson, 1975), or with reference to the unique characters of fragmented forests (Granjon et al, 1996;Marsh and Loiselle, 2003;Medley, 1993;Norconk and Grafton, 2003;Onderdonk and Chapman, 2000;Umapathy and Kumar, 2000;Woodwell, 2002). In both cases, changes in food availability are often a main driving force behind changes in primate densities.…”
Section: Introductionmentioning
confidence: 99%